MODEL PENGEMBANGAN DAN PEMANFAATAN WAKAF TUNAI UNTUK PENDIDIKAN TINGGI (STUDI KASUS WAKAF AMERTA AIRLANGGA) - Syadid, Muhamad; Muammar, Muhammad Arfan (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTThe The increasingly difficult economic conditions require educational institutions at the tertiary level to develop a model for collecting funds from the community, one of which is through cash waqf. Airlangga University already has a model of developing and utilizing campus-based cash waqf. So with this waqf solution the community can be helped especially by students to continue their education. From here the authors are encouraged to conduct research on